# Solve for y -(3y)/4+12=15

-3y4+12=15
Move all terms not containing y to the right side of the equation.
Subtract 12 from both sides of the equation.
-3y4=15-12
Subtract 12 from 15.
-3y4=3
-3y4=3
Multiply both sides of the equation by -43.
-43⋅(-3y4)=-43⋅3
Simplify both sides of the equation.
Simplify -43⋅(-3y4).
Cancel the common factor of 4.
Move the leading negative in -43 into the numerator.
-43⋅(-3y4)=-43⋅3
Move the leading negative in -3y4 into the numerator.
-43⋅-3y4=-43⋅3
Factor 4 out of -4.
4(-1)3⋅-3y4=-43⋅3
Cancel the common factor.
4⋅-13⋅-3y4=-43⋅3
Rewrite the expression.
-13⋅(-3y)=-43⋅3
-13⋅(-3y)=-43⋅3
Cancel the common factor of 3.
Factor 3 out of -3y.
-13⋅(3(-y))=-43⋅3
Cancel the common factor.
-13⋅(3(-y))=-43⋅3
Rewrite the expression.
-1⋅(-y)=-43⋅3
-1⋅(-y)=-43⋅3
Multiply.
Multiply -1 by -1.
1⋅y=-43⋅3
Multiply y by 1.
y=-43⋅3
y=-43⋅3
y=-43⋅3
Cancel the common factor of 3.
Move the leading negative in -43 into the numerator.
y=-43⋅3
Cancel the common factor.
y=-43⋅3
Rewrite the expression.
y=-4
y=-4
y=-4
Solve for y -(3y)/4+12=15

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top